Distinctive Metabolic Signatures in Adrenocortical Tumorigenesis [2] - Duan, Kai; Gucer, Hasan; Kefeli, Mehmet; Asa, Sylvia L.; Winer, Daniel; Mete, Ozgur (Nature Publishing Group, 2017)
…
106th Annual Meeting of the United-States-and-Canadian-Academy-of-Pathology (USCAP) -- MAR 04-10, 2017 -- San Antonio, TX